“GEMAR” Gerakan Masyarakat Anti Narkoba Sebagai Upaya Preventif Berbasis Kultural untuk Pencegahan dan Pemberantasan Peredaran Narkotika dalam Mewujudkan Desa Bersinar di Desa Cisadane Kabupaten Gorontalo Utara - Aryati Abdul; Wirnangsi D Uno; Febriyanti Febriyanti (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Prevention of the spread of drugs in the community is actually a shared responsibility. In this case, all parties including the community itself and the government must play an active role in being aware of the threat of drugs. Research results from the National Narcotics Agency of Gorontalo Province show that as many as 80% of users are teenagers. As many as 13,710 or 5.8% of students and college students have used drugs. The rate of increase in drug users is about 29% each year. Based on Narcotics Case Report Data (LKN) at the National Narcotics Agency of Gorontalo Province (BNNP), the number of drug cases in Gorontalo for 3 years, from 2015 to 2017 there was an increase every year. In 2017 it increased again by 18 LKN (BNNP, 2017). in 2020 it was known that Gorontalo Province was one of the areas which was a red zone for drug trafficking in Indonesia.Therefore, in dealing with this, steps and strategies are needed as an effort to prevent the spread and abuse of drugs in the community.The program given is expected to focus on eradication and prevention, one of which is through preventive methods. By applying a preventive method and supported by a cultural approach by prioritizing the habits and customs of the people of Cisadane Village, then through the Thematic Community Service Program in Shining Village, which will be carried out in Cisadane Village, Kwandang District, North Gorontalo Regency, it is hoped that it can prevent and eradicate the spread and abuse of drugs. among the local community.